2016
DOI: 10.1007/s10973-016-5759-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and physicochemical characterization of solid dispersions containing praziquantel for the treatment of schistosomiasis

Abstract: Praziquantel (PZQ) is an anthelminthic agent active against parasitic flatworms of the Schistosoma type and the most important drug for the treatment and morbidity control of schistosomiasis. In this study, a highperformance liquid chromatography method was employed for quantification of PZQ in the physical mix (PM) and solid dispersion (SD) prepared by Fusion Method utilizing the carriers Gelucire Ò 50/13 and mannitol in ratio 3:1; 1:1; 1:3 PZQ/carrier. Furthermore, PM and SD were characterized by Thermogravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Praziquantel is a poorly water-soluble neutral compound [ 3 ], thus the solubility in gastric (0.1 M HCl) and small intestinal (50 mM phosphate buffer, pH 6.8 with no bile salts) conditions were not statistically different (297 ± 6 µg/mL and 282 ± 149 µg/mL, respectively, Table 1 ). Our findings appear slightly higher but probably not significantly different to those reported in the literature where the solubility of praziquantel in 0.1 M HCl and 200 mM phosphate buffer pH 6.8 was 164 µg/mL and 206 µg/mL, respectively [ 14 ], which could be due to differences in the sample incubation temperatures (23 °C vs. 37 °C in the current study) and the presence of surfactant excipients in the Biltricide ® tablets used in this study. In addition, as depicted in Figure 2 b, once praziquantel was dissolved in the low pH gastric condition, no drug precipitation occurred when the pH of the medium was adjusted to 6.8, suggesting that praziquantel could remain solubilised during gastrointestinal transit.…”
Section: Resultscontrasting
confidence: 71%
“…Praziquantel is a poorly water-soluble neutral compound [ 3 ], thus the solubility in gastric (0.1 M HCl) and small intestinal (50 mM phosphate buffer, pH 6.8 with no bile salts) conditions were not statistically different (297 ± 6 µg/mL and 282 ± 149 µg/mL, respectively, Table 1 ). Our findings appear slightly higher but probably not significantly different to those reported in the literature where the solubility of praziquantel in 0.1 M HCl and 200 mM phosphate buffer pH 6.8 was 164 µg/mL and 206 µg/mL, respectively [ 14 ], which could be due to differences in the sample incubation temperatures (23 °C vs. 37 °C in the current study) and the presence of surfactant excipients in the Biltricide ® tablets used in this study. In addition, as depicted in Figure 2 b, once praziquantel was dissolved in the low pH gastric condition, no drug precipitation occurred when the pH of the medium was adjusted to 6.8, suggesting that praziquantel could remain solubilised during gastrointestinal transit.…”
Section: Resultscontrasting
confidence: 71%
“…Several studies reported the possibility of amorphizing PZQ in the presence of a second compound through the formation of amorphous solid dispersions [ 17 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 50 , 51 , 56 , 57 , 98 , 99 ].…”
Section: Pzq Amorphous Formsmentioning
confidence: 99%
“…The literature provides little information about amorphous forms of PZQ. Several studies reported the possibility of amorphizing PZQ in the presence of a second compound through the formation of amorphous solid dispersions [17,[29][30][31][32][33][34]36,37,50,51,56,57,98,99].…”
Section: Pzq Amorphous Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, miscibility of the active ingredient in the polymer is one of the major issues in amorphous solid dispersions [10][11][12]. To overcome poor miscibility issues, the amount of polymer is increased, and this causes volume enlargement of the dosage form [13,14]. Furthermore, amorphous materials are more hygroscopic than crystalline materials and the glass-transition temperature of most amorphous drugs is lowered, even with only very small water content [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%